DEVELOPMENT OF INDOOR AIR QUALITY SUPERVISION SYSTEMS USING ZIGBEE WIRELESS NETWORKS - DR.M.V.SRUTHI,V.SHANTHI,G PAVANI, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Air quality has received a lot more attention recently as a result of rising environmental consciousness. In this study, a ZigBee wireless network-based indoor air quality monitoring system is suggested. The created system offers a straightforward method for controlling and monitoring indoor air quality (IAQ) for applications in residential buildings. Several sensors are used in the current setup to detect various gases, including carbon monoxide (CO), carbon dioxide (CO2), and fine particulate matter (PM2.5). Additionally, individuals could see the real-time status whenever and anywhere they wanted by utilising the built user interface APP.